Financial Losses Caused by Tax Audit Quality, A Deep Qualitative Findings - Bagus Budi N, Y. Agus; Aryati, Titik (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
One of the whacking concerns experienced by taxpayers in Indonesia is tax audit quality. During the year of 2021, statistical data on tax dispute decisions consisted of 11% not being accepted, 25% rejected, 20% partially accepted, fully accepted 41%, and the other 12%. This statistics figures needs to be studied carefully since it implies several serious issues, one of which is the quality of tax audit. To do so, this research was design to analyze qualitatively using an in-depth interview approach, a piece of the exploration of empirical evidence on tax audit quality in the field of a certain property business experienced by the taxpayer. Using related factors of quality audit, such as input, output and context factors proposed by previous researchers, compared to the previous works, this research offers novelty by combining these factors, with the Indonesian provision of tax audit procedure regulated by Peraturan Menteri Keuangan (PMK) 17/03/2013 (M. K. Republik Indonesia 2013) in conjunction with Peraturan Menteri Keuangan (PMK) 184/03/2015 (M. K. Republik Indonesia 2015) (which was broken down into 10 component and 45 details questions) and Surat Edaran Direktur Jenderal Pajak (SE) 15/PJ/2018 (D. J. P. Republik Indonesia 2018) . There are a number of activities in the process of tax audit works that may affect the quality of tax audit. Some of the features are within the control of the tax auditor such as competencies, knowledge, experiences, but at the same time are out of taxpayer control, such as the audit time limit. The research was carried out by using a deep interview with persons in charge combined with a list answered questionnaire of the taxpayer. Based on the qualitative analysis the results indicate that a poor activities of tax audit quality in term of communication have posed a serious potential financial consequences for the taxpayer in the form of the tax assessment letter for underpayment and the collection letter. The implications of these findings for tax authorities are the urgency in developing tax audit procedure that can improve tax audit quality as mandated by tax provisions, avoiding taxpayers as object of state revenues ambitions. Key words: Financial Losses, Tax Audit Quality, Audit Quality Factors, Tax Audit Procedures